The Legal Ruling on Abortion for Rape Victims from a Maqāṣid al-Sharīʿah Perspective in Government Regulation Number 28 of 2024 on Health - Saipul Nasution; Azmi Hadyan Mumtaza; Mulyono Jamal; Fadhila Tianti Mudi Awalia; Mahadir Mahadir (Lembaga Yasin AlSys, 2026)
Although abortion regulation has received considerable attention in legal and ethical scholarship, studies that specifically examine abortion for rape survivors within Indonesian health law from the perspective of Maqāṣid al-Sharīʿah remain limited. This study aims to analyze the legal framework governing abortion for rape survivors as stipulated in Government Regulation No. 28 of 2024 on Health and to assess its conformity with the objectives of Islamic law. The research employs a qualitative approach with a normative-doctrinal design through library research. Data were collected using documentary analysis of primary legal sources, such as statutes and classical fiqh literature, as well as secondary sources in the form of scholarly books and reputable journal articles, and were analyzed descriptively and analytically using a maqāṣidī taḥlīlī approach focused on the principle of the protection of life (ḥifẓ al-nafs). The findings indicate that the regulation demonstrates substantive alignment with the objectives of Islamic law, particularly in the protection of life, intellect, lineage, and honour, as evidenced, among other things, by the determination of a 14-week gestational limit prior to ensoulment. Nevertheless, the study also identifies various procedural obstacles that may hinder rape survivors’ access to safe and affordable abortion services. The study concludes that the regulation of abortion for rape survivors in this government regulation represents an implementation of the principles of necessity (ḍarūrah) and public interest (maṣlaḥah), and recommends strengthening institutional coordination and health service procedures to ensure effective and just protection for survivors. This study offers both theoretical and practical contributions to the development of Islamic law and reproductive health policy in Indonesia. Keywords: Abortion; Rape Survivors; Maqāṣid al-Sharīʿah; Indonesian Health Law; Islamic Fiqh